An observational study of endoscopic versus microscopic type I tympanoplasty in tubotympanic chronic otitis media in a tertiary health care centre - Chowdhury, Amrita; Das, Shatabdi (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Chronic otitis media (COM) is a widespread disease in the developing countries. It is treated by tympanoplasty, traditionally performed with the microscope which limits the visual field in the deep recesses of the middle ear, especially in narrow external auditory canal. Using endoscope has minimised these difficulties by providing a wide field view with angled magnification, reducing the duration of surgery. The advantages and disadvantages of both techniques is evaluated in our study. Methods: In this observational study, 60 patients of tubotympanic COM between 12-60 years of age with small to medium sized central perforation and air-bone gap of less than 45 decibel were included. They were divided into two groups (group A and group B) of 30 patients each. Group A underwent microscopic type 1 tympanoplasty and group B underwent endoscopic type 1 tympanoplasty. The duration of the surgery, the post-operative improvement in hearing and the graft uptake was analysed after 3 months of surgery. The post-operative hospital stay duration was noted. Results: The post-operative hearing improvement and the graft uptake after 3 months of the surgery was statistically not significant between the two groups. But the mean duration of the operation and the post-operative hospital stay was significantly lower in the endoscopic group with a p value <0.05. Conclusions: Endoscopes are better in otological procedures as it reduces the surgical duration, provides better visibility, lessens the post-operative hospital stay, reducing the economic burden of the patient.